C-Reactive Protein in Atherothrombosis and Angiogenesis - Badimon, Lina; Peña, Esther; Arderiu, Gemma; Padró, Teresa; Slevin, Mark; Vilahur, Gemma; Chiva-Blanch, Gemma (Frontiers in Immunology, 2018)
C-Reactive Protein (CRP) is a short pentraxin mainly found as a pentamer in the circulation, or as non-soluble monomers CRP (mCRP) in tissues, exerting different functions. This review is focused on discussing the role of CRP in cardiovascular disease, including recent advances on the implication of CRP and its forms specifically on the pathogenesis of atherothrombosis and angiogenesis. Besides its role in the humoral innate immune response, CRP contributes to cardiovascular disease progression by recognizing and binding multiple intrinsic ligands. mCRP is not present in the healthy vessel wall but it becomes detectable in the early stages of atherogenesis, and accumulates during the progression of atherosclerosis. CRP inhibits endothelial nitric oxide production, and contributes to plaque instability by increasing endothelial cell adhesion molecules expression, by promoting monocyte recruitment into the atheromatous plaque and by enzymatically binding to modified LDL. CRP also contributes to thrombosis, but depending on its form it elicits different actions. Pentameric CRP has no involvement in thrombogenesis, whereas mCRP induces platelet activation and thrombus growth. In addition, mCRP has apparently contradictory pro-angiogenic and anti-angiogenic effects determining tissue remodeling in the atherosclerotic plaque and in infarcted tissues. Overall, CRP contributes to cardiovascular disease by several mechanisms that deserve an in-depth analysis.